Teacher rewards and their performance: a case study of selected secondary schools in southern division, Kabale municipality - Agnes, Nyinamasiko; John Michael, Edoru (Kabale University Interdisciplinary Research Journal (KURJ), 2023)
Teachers’ performance management is a continuous process for identifying, evaluating and developing the work performance of teachers, so that the goals and objectives of the schools are more effectively achieved, while at the same time benefiting teachers. This study was carried out to establish how teacher rewards influence their performance. A case study of selected secondary schools in Southern Division, Kabale Municipality. The study used cross sectional survey research design. Both quantitative and qualitative approaches were utilized for data collection and analysis Interviews guides were used to collect qualitative data while structured questionnaires instrument was used to collect quantitative data. The study participants were 55 teachers, and 15 head teachers in the selected secondary schools in southern division Kabale municipality. The researcher used systematic analysis method to analyze quantitative data and thematic data analysis to analyze qualitative data. The study established that, teachers’ rewards is highly influenced their performance, and also, financial rewards highly influenced the teachers’ rewards in secondary schools in southern division, Kabale municipality. Finally, it was recommended that the Government of Uganda and the Ministry of Education and sports should provide adequate information and counseling to teachers on creating an environment, inside the classroom and beyond where students can talk openly about their learning, their challenges and what allows them to succeed, teachers’ salaries should be determined according to sector needs as opposed to macro-economic policy requirements if Uganda is to attain the Millennium Development Goals related to Education, there is also a need to continuously engage teachers in the National teachers Union (UNATU) a statutory representative of teachers at all levels in both private and government sectors; this will enable teachers to consult on educational, labor and other relevant issues